Enabling Technology in Optical Fiber Communications: From Device, System to Networking - Yue, Yang; Zhao, Jian; Du, Jiangbing; Li, Zhaohui (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book explores the enabling technology in optical fiber communications. It focuses on the state-of-the-art advances from fundamental theories, devices, and subsystems to networking applications as well as future perspectives of optical fiber communications. The topics cover include integrated photonics, fiber optics, fiber and free-space optical communications, and optical networking.